Experimental Study on Self-Supported Friction Stir Welding on AA5083 Plate Butt Joints - Razak, M.A.A.A. (Springer Science and Business Media Deutschland GmbH, 2021)
Friction stir welding (FSW) has initially been introduced by the TWI in England as an alternative welding method. This research is carried out to determine the optimum welding parameters that contribute to the least root deformation. The rotational speeds of 910Â rpm, 1280Â rpm and 1700Â rpm are used. Meanwhile for the edge preparation, butt, stepped and angle are considered. The selected pin profiles are cylinder, square and triangle shapes. The experiment is tested with nine trials by changing the various combination of welding parameters. A 5Â mm thick AA5083 plate was used as specimen materials. The result is gained by measuring the root deformation under the optical microscope at the joining part. This study is determining the optimum welding for the self-supported friction stir welding at less effect of root deformation for AA5083 plate butt joints. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.